2011
DOI: 10.1109/tpwrd.2011.2148733
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Impulse Response of Distribution Networks With Periodic Tree-Type Topology

Abstract: The main motivation for this paper was to investigate certain asymptotic properties of impulse response in periodic treetype distribution networks owed to the network topology alone, regardless of ohmic losses or material dispersion normally present in practical situations. The research was performed using theoretical analysis of Dirac impulse propagation through a model network, with a focus on topology-related features. Several numerical examples were designed to illustrate the meaning of the main conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Although these ‘ghost’ pulses carry negligible power (Figure ), this is still a good warning that aliasing is something one should not forget. Apart from the aliasing‐caused premature pulses, the impulse response shows very quick decay of received pulse power with time, which is consistent with findings presented in .…”
Section: Examples Of the Stochastic Simulation Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Although these ‘ghost’ pulses carry negligible power (Figure ), this is still a good warning that aliasing is something one should not forget. Apart from the aliasing‐caused premature pulses, the impulse response shows very quick decay of received pulse power with time, which is consistent with findings presented in .…”
Section: Examples Of the Stochastic Simulation Resultssupporting
confidence: 91%
“…All these features make PLC channel modeling rather hard to do. There have been a number of published articles, reporting valued research results and models developed in that field . Such models can be broadly categorized in the following way:In relation to basic modeling approach, there can betime‐domain‐based models andfrequency‐domain‐based models.As for the network dynamics modeling, there can be four types of models:static deterministic,static stochastic (or quasi‐static stochastic),dynamic deterministic, anddynamic stochastic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A technical area where this work can be practically implemented is, for example, power‐line communication systems (PLC) . A brief review of PLC channel modeling can be found in author's previous work published in this journal .…”
Section: Introductionmentioning
confidence: 99%